Investigation of solitary wave solutions for the (3+1)-dimensional Zakharov-Kuznetsov equation - Yokus, Asif; Kuzu, Bulent; Demiroglu, Ugur (World Scientific Publ Co Pte Ltd, 2019)
In this paper, the new traveling wave solutions containing the trigonometric functions, hyperbolic functions and rational functions of (3 + 1)-dimensional Zakharov-Kuznetsov equation are obtained. The graphs of the solution functions are presented by giving specific values to the constants. Numerical solutions are obtained by using finite difference method with new initial condition. Von Neumann's Stability, Consistency and Linear Stability analysis of the equation are performed and L-2, L-infinity norm errors are also examined with the truncation error. The exact solution obtained is presented via numerical solutions and absolute error graphs, and the analysis of exact solution and the numerical solutions are performed. Complex operations and graphical drawings were made using the computer package program.
Keywords: (G '/G, 1/G)-expansion method; (3+1)-dimensional Zakharov-Kuznetsov equation; finite difference method; numerical solutions